The Utilization of Medicinal Plants in the Postpartum Care by Belaban Ella Village's Women of Belaban Resort of Bukit Baka Bukit Raya National Park (TNBBR) - Yeni Mariani; Fathul Yusro; Yuliati Indrayani; Vera Jessika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Belaban Ella village is in the Bukit Baka Bukit Raya National Park (TNBBR) area. The Belaban Ella village community still maintains its local wisdom in using plants to care for women after giving birth. This study aims to describe the local knowledge of the women of Belaban Ella village in utilizing plants for postpartum care. Respondents in this study were selected by purposive sampling and we conducted in-depth interviews with the assistance of a questionnaire. The result showed that women in Belaban Ella village used 25 species of plants in 6 treatment groups. Most of these plants are used to reduce abdominal pain and enhance the mother's breast milk. The most widely used plant family is Zingberaceae; the most used part is the leaves (61%). Grinding (40%) was the most used preparation method, with poultices (32%) and eating (28%) being the predominant method of use. Women in Belaban Ella village still using medicinal plants in postpartum care treatment as an effort to preserve their local knowledge.